Efeitos de vocalizações de co-específicos e do escuro sobre o ritmo circadiano da atividade motora em sagüis (Callithrix jacchus) - Silva, Crhistiane Andressa da (2007)
The principal zeitgeber for most of species is the light-dark photocycle (LD), though other environment factors as food availability, temperature and social cues may act. Daily adjustment of the circadian pacemaker may result from integration of environmental photic and non-photic cues with homeostatic cues. Characterization of non-photic effects on circadian timing system in diurnal mammals is scarce in relation to nocturnal, especially for ecologically significant cues. Thus, we analyzed the effect of conspecific vocalizations and darkness on circadian activity rhythm (CAR) in the diurnal primate Callithirx jacchus. With this objective 7 male adults were isolated in a room with controlled illumination, temperature (26,8 ± 0,2°C) and humidity (81,6 ± 3,6%), and partial acoustic isolation. Initially they were under LD 12:12 (~300:2 lux), and subsequently under constant illumination (~2 lux). Two pulses of conspecific vocalizations were applied in total darkness, separated by 22 days, at 7:30 h (external time) during 1 h. They induced phase delays at circadian times (CTs) 1 and 10 and predominantly phase advances at CTs 9 and 15. After that, two dark pulses were applied, separated by 14 days, during 1 h at 7:30 h (external time). These pulses induced phase delays at CTs 2, 3 and 18, predominantly phase advances at CTs 8, 10 and 19, and no change at CT 14. However, marmosets CAR showed oscillations in endogenous period and active phase duration influenced by vocalizations from animals outside the experimental room, which interfered on the phase responses to pulses. Furthermore, social masking and relative coordination with colony were observed. Therefore, phase responses obtained in this work cannot be attributed only to pulses. Afterwards, pulses of conspecific vocalizations were applied in total darkness at 19:00 h (external time), during 1 h for 5 consecutive days, and after 21 days, for 30 consecutive days, on attempt to synchronize the CAR. No animal was synchronized by these daily pulses, although oscillations in endogenous period were observed for all. This result may be due to habituation. Other possibility is the absence of social significance of the vocalizations for the animals due to random reproduction, since each vocalization has a function that could be lost by a mixture of sounds. In conclusion, conspecific vocalizations induce social masking and relative coordination in marmosets CAR, acting as weak zeitgeber